UN EJEMPLO DE ESTRATEGIA RETORICA: LA PARADOJA EN EL LENGUAJE PUBLICITARIO - Díez Arroyo, Marisa (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Although the bulk of studies devoted to advertising has risen in recent years, most of the works continue to be devoted to advertising as mass-media. In this paper I would like to look at this field of communication giving prominence to the discursive strategies used in the elaboration of the slogan, with special emphasis on paradox as a rhetorical device. My aim is to show how copywriters have fought out their way to regain the consumer's trust, a trust which has been undermined by the proliferation of messages. This task will be carried out paying attention to the language used by advertisers in written slogans. As a result, emphasis will be placed on incongruity at two levels: the semantic and the pragmatic. Given the special characterization of advertising communication, the methodology employed makes use of two main perspectives. Firstly, the rhetorical perspective will help us understand the keys to persuasion, as well as the effect sought by flouting stylistic rules. Secondly, the pragmatic perspective, on surveillance of Sperber & Wilson's Relevance Theory, will offer an account of the role played by inferences, weak implicatures, contextual effects or processing effort in advertising communication.